Active Components of Traditional Chinese Medicinal Material for Multiple Myeloma: Current Evidence and Future Directions - Yu, Chao-Chao; Li, Yi; Cheng, Zhao-Jun; Wang, Xi; Mao, Wei; Zhang, Ying-Wen (Frontiers in Pharmacology, 2022)
Multiple myeloma (MM) is a hematological malignancy characterized by clonal expansion of plasma cells in bone marrow, leading to the overproduction of monoclonal immunoglobulins. The clinical manifestations resulting from monoclonal proteins and malignant cells include signs of end-organ damage, such as hypercalcemia, renal failure, anemia, and bone lesions. Despite improvement in the survival of MM patients with use of myeloma-targeted and immunomodulatory therapies, MM remains an incurable disease. Moreover, patients with relapsed or refractory MM show poor survival outcomes. In recent years, there has been a growing interest in the use of traditional Chinese medicinal materials (TCMMs) for management of a wide spectrum of diseases. The bioactive ingredients derived from TCMMs hold great potential for the development of anticancer drugs. Here we summarize the evidence of the pharmacological effects of the active components in TCMMs on MM, including curcumin, resveratrol, baicalein, berberine, bufalin, cinobufagin, gambogic acid, ginsenoside, icariin, daidzin, formononetin, polysaccharides extracts from Hedyotis difus, and scutellarein. Available evidence indicates that the anti-MM effects of these bioactive ingredients are mediated via regulation of proliferation, apoptosis, autophagy, cell cycle, osteogenic differentiation, and drug resistance. In the future, the underlying mechanisms of the anti-MM effects of these components should be further investigated. Large-scale and well-designed clinical trials are also required to validate the efficacy of these bioactive constituents for MM.